Clifford's blues - Williams, John A. 1925-2015 (Coffee House Press, 1998)
A black man recounts life in a World War II concentration camp. He is Clifford Pepperidge, a gay pianist from New Orleans, working in night clubs in Germany. Arrested for being a homosexual, he is deported to Dachau where a Nazi officer employs him to play the piano at parties. The officer is gay and Pepperidge must sleep with him. A tale of degradation in order to survive, by the author of Captain Blackman.
Keywords: Dachau (Concentration camp) -- Fiction; Konzentrationslager Dachau; Schwarze. USA; African Americans -- Fiction; Americans -- Europe -- Fiction; Concentration camps -- Fiction; Gefangener; Schwarze; Europa; Fiktionale Darstellung; Diary fiction